Cherie Y. Hamilton: Cuisines of Portuguese Encounters - Jaine, Tom (Petits Propos Culinaires, 2024)
Cherie Y. Hamilton: Cuisines of Portuguese Encounters: Hippocrene Books, New York, 2001: ISBN 0-7818-0831-6: 377 pp., b/w illus., h/b, $24.95.